Laika - Abadzis, Nick. (First Second, 2007)
This is the journey of Laika, the abandoned puppy destined to become Earth's first space traveler. With the blending of fact and fiction, this story intertwines three compelling lives. Along with Laika, there is Korolev, a driven engineer at the top of the Soviet space program and Yelena, the lab technician responsible for Laika's health and life.